Reaksi Padi Hibrida Introduksi terhadap Penyakit Hawar Daun Bakteri dan Hubungannya dengan Hasil Gabah - Sudir, Sudir; Sutaryo, Bambang (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
A research was conducted to determine the response of introduced hybrid rice varieties to bacterial leaf blight (BLB) disease caused by Xanthomonas oryzae pv. oryzae (Xoo) and its relationship to grain yields The trial was planted at the Sukamandi Experiment Station during the wet season (WS) 2008/09 and at Kuningan Experiment Station in the dry season (DS) of 2008 and WS 2008/09. Fourteen rice genotypes consisting of 9 introduced hybrid rice varieties from China, variety Code (resistant check), IR64 (susceptible check), and Intani-2 Batang Samo (hybrid checks), and Ciherang (inbred check) were evaluated. The experiment was laid out in a completely randomized block design with three replications. The trial at Kuningan, a BLB endemic area, was carried out with an assumption that grain yield performances of the 14 rice genotypes would be influenced by be severity of the BLB. Data from the greenhouse trial showed that reactions of the introduced hybrid rice to Xoo pathotype III varied from moderately resistant to resistant, moderately susceptible to susceptible to Xoo pathotype IV, and resistant to moderately Xoo pathotype VIII. In the field, the severity of the BLB disease ranged from 4.2% on Sembada B9 to 11.4% on WCR115 in the DS 2008, and from 4.9% on Sembada B9 to 30.4% on WCR073 in the WS 2008/09. In the DS 2008, the highest grain yield was obtained from Sembada B9 (9.79 t/ha) followed by Sembada B8 (9.6 t/ha), Sembada B3 (9.26 t/ha), and Sembada B5 (9.79 t/ha). In the WS 2008/2009, the highest grain yield was also obtained from Sembada B9 (8.85 t/ha) followed by Sembada B8 (8.80 t/ha), Sembada B3 8.63 t/ha), and Sembada B5 (7.77 t/ha). These four rice hybrids were resistant to Xoo pathotype III. The overall average rice yield in the DS, was higher than that in the WS 2008/2009, presumably as a result of the lower severity BLB disease.